2022
DOI: 10.1155/2022/5140259
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess: A Rare Clinical Case with Oral Etiology

Abstract: Brain abscess is a very rare condition but has a significant mortality rate. The three main routes of inoculation are trauma, contiguous focus, and the hematogenous route. The odontogenic focus is infrequent and is usually a diagnosis of exclusion. This paper presents a brain abscess case proven to be of dental origin, caused by Actinomyces meyeri and Fusobacterium nucleatum. This case highlights the risk underlying untreated dental disease and why oral infectious foci removal and good oral health are essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Several studies have demonstrated the involvement of bacteria of the oropharyngeal flora in the pathophysiology of many systemic, cardiovascular and cerebral diseases [3, 8]. Dental infection, and particularly periodontitis and dental caries are a rare but possible starting point for brain abscesses through haematogenous spread [1–6, 8, 11–14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the involvement of bacteria of the oropharyngeal flora in the pathophysiology of many systemic, cardiovascular and cerebral diseases [3, 8]. Dental infection, and particularly periodontitis and dental caries are a rare but possible starting point for brain abscesses through haematogenous spread [1–6, 8, 11–14].…”
Section: Discussionmentioning
confidence: 99%
“…The odontogenic abscess also represents a source of spread especially through a hematogenous route, though this is exceedingly rare and is usually a diagnosis of exclusion. [ 1 , 11 ] However, the location of brain abscess near a traumatic fracture with dural violation raises suspicion for association of this orbital fracture caused by blunt trauma with intracranial abscess. A careful review of a patient’s history and risk factors is necessary to determine the source of infection and adequate treatment, whether the infection be traumatic, iatrogenic, or otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other strict anaerobic bacteria, F. nucleatum possess NADH oxidase endowing them with a limited ability to survive in oxygenated environment [ 117 ]. In addition to its implication in periodontal disease [ 118 ], F. nucleatum is capable of systemic dissemination and causing extra-oral infections, such as brain, liver, spleen, and lung abscesses, septicemia related infections, pelvic inflammatory disease, and intrauterine infections [ 119 , 120 , 121 , 122 , 123 , 124 ]. F. nucleatum is equipped with a variety of adhesins that enable it to adhere to various microorganisms.…”
Section: Virulence Factors Of Periodontal Pathogens and Their Associa...mentioning
confidence: 99%